One-pot sequential synthesis of tetrasubstituted thiophenes via sulfur ylide-like intermediates - Kim, Jun Ki; Lim, Hwan Jung; Jeong, Kyung Chae; Park, Seong Jun (Beilstein Journal of Organic Chemistry, 2018)
Herein, we describe a novel approach for the practical synthesis of tetrasubstituted thiophenes 8. The developed method was particularly used for the facile preparation of thienyl heterocycles 8. The mechanism for this reaction is based on the formation of a sulfur ylide-like intermediate. It was clearly suggested by (i) the intramolecular cyclization of ketene N,S-acetals 7 to the corresponding thiophenes 8, (ii) 1H NMR studies of Meldrum’s acid-substituted aminothioacetals 9, and (iii) substitution studies of the methoxy group on Meldrum’s acid containing N,S-acetals 9b. Notably, in terms of structural effects on the reactivity and stability of sulfur ylide-like intermediates, 2-pyridyl substituted compound 7a exhibited superior properties over those of others.
Keywords: 5-(heterocyclic)thiophenes; one-pot sequential synthesis; sulfur ylide; tetrasubstituted thiophene